The importance of multimodal CT examination in stroke mimics diagnosis: design of prospective observational multicentre study - Dvorníková, Kateřina; Kunešová, Veronika; Ely, Marcela; Ostrý, Svatopluk; Čábal, Martin; Reiser, Martin; Machová, Linda; Pavlínová, Markéta; Kondé, Adéla; Eliáš, Pavel; Jonszta, Tomáš; Havelka, Jaroslav; et al. (Frontiers in Neurology, 2024)
Introduction. Non-contrast CT and CT angiography are the gold standard in neuroimaging diagnostics in the case of suspected stroke. CT perfusion (CTP) may play an important role in the diagnosis of SM, but currently it is not a standard part of the stroke diagnostic procedure.The project is a multicentre prospective observational clinical research focused on refining diagnostics of stroke and stroke mimics (SM) in hospital care.To evaluate the degree of specificity and sensitivity of multimodal CT (NCCT, CTA, CTP) in the diagnosis of stroke mimics versus stroke.Methodology. We will include into the study 3000 patients consecutively admitted to the Comprehensive Stroke Centres with a diagnosis of suspected stroke. On the basis of clinical parameters and results of multimodal CT and MRI, the diagnosis of stroke and SM will be established. In order to clarify the significance of the use of the multimodal CT scan, the analysis will include a comparison of the blinded results for each imaging scan performed by radiologists and AI technology and a comparison of the initial and final diagnosis of the enrolled patients. Based on our results will be compared of the economic indicators and costs that will be saved by not providing inadequate treatment to patients with SM.The expected outcome is to present an optimised diagnostic procedure that results in a faster and more accurate diagnosis, therefore eliminating the risk of inadequate treatment in patients with stroke mimics.